Hubungan Persepsi Kecantikan Tradisional, Persepsi Kecantikan Ideal dan Citra Merek Kosmetik Sariayu dengan Minat Beli Produk Kosmetik Sariayu - Aike Ingget Pratiwi; Tandiyo Pradekso; Djoko Setyabudi (Interaksi Online, 2021)
Although Sariayu cosmetic products have been established for a long time, in 2016 until 2020, Sariayu’s cosmetic products have a lower Top Brand Index (TBI) than its 2 competitors, Wardah and Viva. Furthermore in the last 2 years, some of the products are not included in the Top Brand. This result is not in accordance with the previous and current efforts done by Sariayu to promote its produtcs and values. Starts with being main sponsor at Miss Indonesia, Miss Earth Indonesia, launched some innovations, and created web-series. Researcher presumes that Top Brand Index (TBI) drop is not solely caused by the communication strategy made by Sariayu but the shifting meaning of beauty and value carried by Sariayu with what beauty mean in today's society. This research aims to explain the linkages between traditional beauty perceptions, ideal beauty perceptions, and Sariayu cosmetics brand image with Sariayu cosmetics purchase intention. This research uses quantitative research with explanatory research type. The population in this study is women who lives in Semarang City, aged 17-35 years, and know Sariayu’s cosmetic products. This study uses non-probabililty sampling techniques with 100 respondents. Chi Square is used as statistical test. The theories used as references are the Self Congruity Theory by Sirgy and The Consumer Decision-Making Theory by George E. Belch and Michael A. Belch. The result showed that there is no linkages between traditional beauty perception with Sariayu cosmetics purchase intention (significance value 0.098 > 0.05), there is linkages between the ideal beauty perceptions with Sariayu cosmetics purchase intention (significant value 0.000 < 0.05), as well as there is no linkages between Sariayu cosmetic brand image with Sariayu cosmetics purchase intention (significance value 0.077 > 0.05.).